LEGAL SYSTEM AS A LEGAL PARAMETER OF FORMING AND DEVELOPING CIVIL SOCIETY IN RUSSIA - Bainiyazova, Зульфия Сулеймановна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2013)
In this article the author states and substantiates a proposition that a legal system defines the outline of civil society legal development. Forming and developing civil society depends much on the organization and functioning of the legal system. The legal system provides rights and personal freedom in civil society.